MO237A SERUM COMPLEMENT ABNORMALITY REVEALED BY THROMBOTIC MICROANGIOPATHY DURING INTERFERON TREATMENT OF MULTIPLE SCLEROSIS. (29th May 2021) - Rihem, Dahmane; Sanda, Mrabet; Raja, Boukadida; Yosra, Guedri; Asma, Fradu; Wissal, Sahtout; Awatef, Azzabi; Narjess, Ben aicha; Dorsaf, Zellama; Abdellatif, Achour
Abstract: Background and Aims: Multiple sclerosis (MS) is a chronic and potentially disabling disease of the central nervous system and is the leading cause of non-traumatic neurological disability in young adults. Beta interferons (IFN-β) are the most-widely prescribed medications for this disease. Despite good overall long-term safety data with prolonged use of this group of drugs, they can rarely cause serious and sometimes life threatening adverse effects. We report a case of thrombotic microangiopathy (TMA) in a patient treated with IFN-β-1a for 03 years. The serum complement study revealed a decrease in Factor I. Method: Case report Results: A 28-year-old man was diagnosed with relapsing remitting multiple sclerosis in 2007. Subcutaneous IFNβ-1a 44 μg was commenced three times a week in 2017. He had not had a relapse since 2012. In July 2020, he was admitted to intensive care unit for a status epilepticus associated with severe arterial hypertension and then transferred to our department for management of malignant arterial hypertension with acute renal failure.On examination, he did not present any neurological disorder but had very unbalanced blood pressure under triple therapy. Biology had shown an hemoglobin at 9, 7 g / dl; no thrombocytopenia with a collapsed haptoglobin, very high LDH with absence of schizocytes, positive non-specific ANCA and proteinuria at 7g/24hour. The renal puncture biopsy showed chronic vascular and glomerular TMA with IgG and fibrinogen deposits. The course was marked by the rapid deterioration of renal function. The patient received flash corticosteroid therapy 10 mg / kg IV for 3 consecutive days switched to oral corticosteroid therapy 0.5 mg / kg / day and received supportive treatment including plasma exchange and hemodialysis. He was discharged after a prolonged admission. At follow-up 6 months later, he had not regained kidney function and remained on hemodialysis and was still taking 3 antihypertensive treatments. A follow-up immunological workup showed a decrease in Factor I: 26, 83 mg/l (32, 3-87, 5). The patient was diagnosed with drug-induced TMA favored by complement abnormality. Treatment with Eculizimab is under discussion. Conclusion: IFN-β are main therapies for relapsing remitting multiple sclerosis. Serious complications are relatively rare and IFN-βs are generally considered to be safe. Nevertheless, rare serious and/or life-threatening side effects have been reported such as TMA. This can, as in our patient, be favored by an abnormality of the serum complement. Thus, a study on serum complement would be recommended before IFN-β prescription.